Tipologi Pemikiran Fikih Nahdhatul Ulama - Salman Abdul Muthalib (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
This paper examines the typology of Nahdlatul Ulama fiqh thinking as one of the major religious organizations in Indonesia. A religious organization inherently shares a basic foundation with the society itself, thereby encountering no challenges in carrying out various organizational activities. This paper aims to determine whether this organization falls into the categories of tajdid, salaf, or tamazhub. Based on the analysis of its articles of association, muktamar (major assembly), and fatwas, it can be concluded that Nahdlatul Ulama was initially categorized as adhering to a particular school of jurisprudence (mazhab). However, since the 1990s, Nahdlatul Ulama has not only followed the opinions of a single school of thought but has also studied the methods pursued by scholars of that school.